Coping with COVID-19: social representations underlying blaming processes and fear. Issue 7 (3rd July 2022) - Idoiaga Mondragon, Nahia; Berasategi Sancho, Naiara; Ozamiz-Etxebarria, Naiara; Alonso Saez, Israel
Abstract: Objective. This study examines how people socially represent the COVID-19 pandemic in the early stage of the health crisis in Europe. Specifically, this research analyses the days before and immediately after the declaration of the state of emergency in Spain, which resulted in the entire population being placed in lockdown. Design. For this purpose, we used the Grid Elaboration Method for free association elicited by the word "coronavirus". This exercise was completed by 1037 people from Spain. Main Outcome Measures . Responses were analysed using Iramuteq software for lexical analysis. Results. Before the state of emergency and lockdown, there was a repeat of many of the emotional and cognitive patterns seen in previous pandemics such us upward and downward blaming or feelings of anger and emotional fatigue. However, outward blaming patterns towards peers also emerged. Moreover, in the period following lockdown, we noted the emergence of new representations and emotions such as paralyzing distrust or resilience. Similarity analysis revealed that the "fear of pandemic" hides a wide variety of emotions. Conclusion. Understanding the blaming and fear processes that are linked to the emergence of the COVID-19 pandemic in Spain offers us practical implications for coping with the challenge of this new crisis.